Dextrose gels for neonatal transitional hypoglycemia: What are we giving our babies?. Issue 2 (5th February 2019) - Solimano, Alfonso; Kwan, Eddie; Osiovich, Horacio; Dyer, Roger; Elango, Rajavel
Abstract: Transitional hypoglycemia is common in at-risk newborns, frequently resulting in therapeutic interference with bonding and breastfeeding; 40% dextrose gel massaged to the buccal mucosa has been shown to decrease hypoglycemia <2.6 mmol/L and NICU admissions. However, in the absence of a newborn-specific product, over-the-counter diabetes-care products with poorly documented composition are being used for neonates. We analyzed the carbohydrate content, and compared composition of the two commercially available gels in Canada, Dex4 and Insta-Glucose. We found that the glucose concentrations were significantly different from the expected 40% glucose, and that they contain artificial colorants, flavours and preservatives. In addition, we observed inconsistent concentration differences within each tube when aliquotes from the top, middle, or bottom were measured. There is a need for a custom made neonatal dextrose gel dispensed in unit dose vials, with a standardized concentration of glucose, and without chemical substances one would generally not recommend administering to newly born infants.